REIMAGINING BUSINESS ETHICS THROUGH CHIARA LUBICH’S ECONOMY OF COMMUNION: A PHILOSOPHICAL AND SPIRITUAL INQUIRY - Mfugale, Castor (International Journal Multidisciplinary (IJMI), 2026)
Objective: The twenty-first century global economy is marked by ethical turbulence, characterized by corruption, inequality, labor exploitation, and environmental degradation. Mainstream capitalist paradigms, shaped by utilitarian rationality and the Protestant ethic, have prioritized profit and efficiency over human dignity and social cohesion, contributing to systemic moral and social disintegration. This study critically examines the Economy of Communion (EoC), a values-based economic model inspired by Chiara Lubich and developed within the Focolare Movement, which integrates deontological ethics, Thomistic virtue, and mystical spirituality into business practice. Method: Employing a conceptual and qualitative methodology, the research synthesizes philosophical, theological, and empirical literature to analyze the historical origins, ethical principles, and operational dynamics of the EoC. Results: Findings indicate that its core pillars gratuitousness, reciprocity, and social responsibility enable enterprises to align profitability with human flourishing, community solidarity, and long-term sustainability. Empirical evidence demonstrates that EoC enterprises achieve robust financial performance while fostering social cohesion and participatory governance. Novelty: The study concludes that the EoC offers a practical and replicable framework for reimagining business as a moral vocation, illustrating that ethics and profitability are mutually reinforcing rather than mutually exclusive. Adoption of EoC principles provides a strategic and ethical imperative for sustainable, human-centered, and socially responsible business practices in contemporary economies.